The Value of Multimodality PET/CT Imaging in Detecting Prostate Cancer Biochemical Recurrence - Jiang, Jie; Tang, Xiaoxia; Pu, Yongzhu; Yang, Yong; Yang, Conghui; Yang, Fake; Tian, Yadong; Li, Jindan; Sun, Hua; Zhao, Sheng; Chen, Long (Frontiers in Endocrinology, 2022)
Prostate cancer (PCa) induced death is the predominant cause of cancer-related death among men in 48 countries. After radical treatment, biochemical recurrence has become an important factor for prognosis. The early detection and diagnosis of recurrent lesions are very helpful in guiding treatment and improving the prognosis. PET/CT is a promising method for early detection of lesions in patients with biochemical recurrence of prostate cancer. This article reviews the progress of the research on PET/CT in the PCa biochemical recurrence and aims to introduce new technologies and provide more direction for future research.